The Influence of Postpartum Exercise on Uterine Involution Speed in Postpartum Mothers - Fatimah; Harahap, Maryam Latifah; Siregar, Rahmah Juliani; Suryani, Elvi (PT Inovasi Pratama Internasional, 2024)
The postpartum period begins a few hours after the birth of the placenta and continues until approximately 6 weeks after childbirth. According to the World Health Organization (WHO), an estimated 830 women die every day due to complications from pregnancy and childbirth. In 2015, approximately 303,000 women died during pregnancy, childbirth, or in the postpartum period. The theme of this study is to investigate the influence of postpartum exercise on the speed of uterine involution among postpartum mothers at BPM Mona Durryah Siregar, SKM in North Padangsidimpuan District. This study utilized a quasi-experimental design with a pretest-posttest only design. The research was conducted at BPM Mona Durryah Siregar, SKM in North Padangsidimpuan District. The population consisted of 10 postpartum mothers, with a sample size of 10. Data analysis included univariate and bivariate analyses. The results of the study showed a significant decrease in uterine fundus height among the 10 respondents, with a percentage of 2.70%. None of the respondents experienced subinvolution after the postpartum exercise intervention. However, 10 respondents faced challenges in decreasing uterine fundus height both before and after the intervention. The Wilcoxon ρ-value test of 0.004 indicates that postpartum exercise influences the speed of uterine involution among postpartum mothers. The implications of this study suggest that implementing postpartum exercise therapy can accelerate uterine involution among postpartum mothers. It is recommended that these findings be used to develop counseling programs related to postpartum exercise at BPM Mona Durryah Siregar, SKM.